Telaah Hadits Hak-Hak Istri Dalam Rumah Tangga - Khoiri, M. Alim (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2021)
Conflict in the household is a normal thing. Usually, conflicts in the household are caused by husbands' and wives' rights that have not been fulfilled. This study aims to examine the quality of the hadith regarding the rights of wives in the household. The literature review method is used in this research. Researchers found several matan of hadiths that explain the rights of a wife in the household narrated by Abu Dawud. The hadith that describes the rights of the wife in the household, the history of Abu Dawud has a good sanad quality, has a good matan quality, and meets the criteria of sahih hadith. Furthermore, this study's results will benefit society; especially will benefit husbands, to fulfill their wives' rights in the household.